The Integration Of Among (Instantiating) System In The Inclusive Education At Taman Muda Ibu Pawiyatan Primary School Yogyakarta - Eka Tusyana; Wina Calista (Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2019)
The research aim is to describe the integration of among systems in inclusive education at Taman Muda Ibu Pawiyatan Primary School Yogyakarta. This research utilized case study method with a qualitative approach. The data collection instruments were interview, observation, and documentation. The result indicates that among systems in inclusive education at Taman Muda Ibu Pawiyatan Primary School Yogyakarta is integrated into classroom and outing class learning activities. Among system in the classroom learning activity is integrated by teachers to not only provide material but also advise and habituation to students such as maintaining a good attitude to peers. Teachers apply the jigsaw method in learning, which is aimed to train regular students or students with special needs to implement the attitudes of being responsible, cooperative, and respecting other people’s opinions. Teachers do not demand students with special needs to compare their ability with regular children to achieve scores based on Minimum Criteria of Mastery Learning (or usually called Kriterai Ketuntasan Minimal/KKM). They open the opportunity to students, especially they who have special needs at inclusive school to train their independence without continuously depending on guardian. In the among the system of outing class learning, teachers apply three systems, which are karawitan (playing a java musical instrument), dance art, and scout.